Cyclical and secular changes in the world economy : an essay in interpretation of the new phenomena in the world economy - Kemenes, Egon. (Budapest : Hungarian Scientific Council for World Economy, 1981)
This book explains some of the positives changes around the world economy. it reveal some of the new task and changes for the economist.
Includes bibliographical references.
asm; 13/02/19
Loans
Keywords: Economic history; Economic history; Economics